Word Level, Above Level, Grammatical Level, Textual, Pragmatics Level Non-Equivalence: Problem and Strategy - Andi Rustandi; Syafryadin Syafryadin; R. Bunga Febriani (Yayasan Karinosseff Muda Indonesia, 2021)
This study is aimed at elaborating the non-equivalences in the word level, above level, grammatical level, textual level, pragmatics level in translation process. This study employed the two research questions i.e. what are the types non equivalences emerge in the translation process? and what are the problems and strategy used by the translator that emerge in translation process?. Covering these questions, this study used descriptive qualitative approach by using the library research to gain some references of types of non-equivalences, problems, and strategy used in the object of the study. The result revealed various types of non-equivalences and problems emerge from the translation process and some strategies also used by the translator to cover the problematic issues on the non-equivalence in translation process.